Contribution of microRNA 24-3p and Erk1/2 to interleukin-6-mediated plasma cell survival - Gabler, Jessica; Wittmann, Jürgen; Porstner, Martina; Renz, Harald; Jäck, Hans-Martin; Abram, Melanie; Zemlin, Michael (European journal of immunology, 2013)
Plasma cells can survive for long periods and continuously secrete protective antibodies, but plasma cell production of autoantibodies or transformation to tumor cells is detrimental. Plasma cell survival depends on exogenous factors from the surrounding microenvironment, and largely unknown intracellular mediators that regulate cell homeostasis. Here we investigated the contribution of the microRNA 24-3p (miR-24-3p) to the survival of human plasma cells under the influence of IL-6 and SDF-1α (stromal cell derived factor 1), both of which are bone marrow survival niche mediators. Deep sequencing revealed a strong expression of miR-24-3p in primary B cells, plasma blasts, plasma cells, and in plasmacytoma cells. In vitro studies using primary cells and the plasmacytoma cell line RPMI-8226 revealed that (i) expression of miR-24-3p mediates plasma cell survival, (ii) miR-24-3p is upregulated by IL-6 and SDF-1α, (iii) IL-6 mediates cell survival under ER stress conditions via miR-24-3p expression, and (iv) IL-6-induced miR-24-3p expression depends on the activity of the MAP kinase Erk1/2. These results suggest a direct connection between an external survival signal and an intracellular microRNA in regulating plasma cell survival. miR-24-3p could therefore be a promising target for new therapeutic strategies for autoimmune and allergic diseases and for multiple myeloma.
Gesehen am 26.01.2021